Novelties in the pharmacological approaches for chronic heart failure: new drugs and cardiovascular targets - Correale, Michele; Tricarico, Lucia; Croella, Francesca; Alfieri, Simona; Fioretti, Francesco; Brunetti, Natale Daniele; Inciardi, Riccardo M.; Nodari, Savina (Frontiers in Cardiovascular Medicine, 2023)
Despite recent advances in chronic heart failure (HF) management, the prognosis of HF patients is poor. This highlights the need for researching new drugs targeting, beyond neurohumoral and hemodynamic modulation approach, such as cardiomyocyte metabolism, myocardial interstitium, intracellular regulation and NO-sGC pathway. In this review we report main novelties on new possible pharmacological targets for HF therapy, mainly on new drugs acting on cardiac metabolism, GCs-cGMP pathway, mitochondrial function and intracellular calcium dysregulation.